Identifikasi Potensi Daerah Terdampak Pencemaran Udara di Indonesia Menggunakan Pendekatan Model WRF-Chem - Pratama, Alvin (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Air pollution is a major environmental problem in Indonesia, especially in urban and industrial areas. This study aims to identify regions potentially affected by air pollution using the WRFChem model. Simulations were conducted to analyze the distribution of PM10 pollutants in July, during the Australian monsoon. The simulation results show that most regions in Indonesia remain within safe limits, with PM10 concentrations below the threshold of 75 μg/m³. However, several major cities on the island of Java, such as Jakarta, Tangerang, Yogyakarta and Surabaya, experienced elevated concentrations exceeding the air quality standard. In addition, monsoon wind patterns caused pollutants to spread northward, increasing concentrations in the provinces of Lampung and South Sumatra. These findings highlight the importance of monitoring air quality and implementing mitigation strategies to reduce the impact of air pollution on public health and the environment.